TRADITIONAL PESANTREN CURRICULUM AND LEARNING CULTURE AS TAFAQQUH FIDDÎN IN ROUDHOTUL ULUM ISLAMIC BOARDING SCHOOL - Desi Rosyita; Aat Royhatudin; Budiana Budiana (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2021)
The traditional pesantren curriculum has unique and prominent characteristics. However, in an ineffective learning process, the close relationship with kiai/school leader can hinder the development of the culture and understanding of the religion of santri/students' Tafaqquh Fiddîn, especially in the Roudhotul Ulum Cidahu Pandeglang Islamic Boarding School. The purpose of this research is how the traditional pesantren curriculum and the learning culture of students can realize the Tafaqquh Fiddîn of the santri at the Roudhotul Ulum Cidahu Pandeglang Islamic Boarding School, namely the relationship between the students and the kiai is well developed. The methodology used in this research is qualitative research. The approach used is a case study at the Salafi Islamic Boarding School Roudhotul Ulum Cidahu Pandeglang. The results of this study prove that the traditional pesantren curriculum at the pesantren is able to realize a complete, balanced understanding and practice of Islamic religious values ??between the world and the hereafter. The learning culture is formed on the basis of tafaquh fiddîn orientation by getting used to prayer, tadarus, and asking for the benefits of knowledge, which until now is still run consistently. Then, the understanding of their religiousity can be seen from the polite personality of the santri, the professional competence of the santri and the dissemination of knowledge with good behavior and character as taught in the traditional pesantren Cidahu Pandeglang.